IMPLEMENTASI LOGIKA FUZZY DALAM PERANCANGAN SISTEM PENGAMBILAN KEPUTUSAN USULAN PEMASANGAN LISTRIK BERDASARKAN DISTRIBUSI BEBAN LISTRIK - Maryaningsih, Maryaningsih; Haryadi, Bambang Herawan; Suryana, Eko (Jurnal Media Infotama, 2013)
System of decision making is a way of leadership or action to solve the problems faced by the selection of one among the possible alternatives. In this study researchers using Fuzzy Logic method because the researchers are using fuzzy logic to determine the weights of criteria and desire in determining who the decision-making stage in the installation of a new power station in PT PLN (Persero) Rayon Nusa Indah Bengkulu. In taking decisions researchers also use the Visual Basic 6.0 programming language, because by using Visual Basic 6.0 programming language researchers can easily in decision-making.